Literature Review: The Impact of Health Facility Accreditation on the Effectiveness of Management Oversight Systems - Qurrotaayun, Syifa Fitriana; Sabilla, Rahma Nasywa; Lestari, Dian Mardiana; Anastasia, Virgine Weby; Noufalwafiq, Muhamad Rama; Siti Aisyah; Harry Fauzi (Jurnal Kesehatan Cendikia Jenius, 2025)
The quality of healthcare services is a crucial indicator in ensuring patient safety, and accreditation serves as a strategic instrument to achieve this goal. Accreditation functions as a framework to assess and improve the effectiveness of management oversight in healthcare facilities. This study aims to identify and analyze the impact of accreditation on the effectiveness of management oversight systems. The research design is a literature review by analyzing 12 national and international articles from the Google Scholar database published between 2014 and 2024. Data collection was conducted systematically using the PICO approach, with predetermined inclusion and exclusion criteria. Thematic analysis was applied to examine relevant study findings. Results show that accreditation enhances communication among healthcare workers, compliance with procedures, service documentation, and safety culture. However, challenges such as limited resources, organizational cultural differences, and high implementation costs remain obstacles. In conclusion, accreditation has proven to be an effective managerial tool for improving service quality and management oversight systems in healthcare facilities. It is recommended that to ensure its sustainability, strengthening human resource capacity, responsive policy support, and continuous technical assistance—especially in resource-limited areas—are essential.